Colicins E7 and E8 degrade DNA in sensitive bacteria - Smarda, J; Smarda, J; Vrbická, Z (Folia microbiologica, 1990)
The primary target of colicin E7 in sensitive bacteria are their DNA molecules. In agarose gel electrophoresis of lysates of cells treated with colicin E7, both chromosomal and plasmid DNA bands disappear, in direct relation to E7 concentration and to the duration of treatment. DNA degradation is followed by a cessation of DNA synthesis. In E7-immune bacteria, no damage to DNA due to colicin E7 occurs. The mode of action of colicin E7 thus appears to be equal to that of colicin E2. Also, colicin E8 causes a distinct damage to chromosomal and plasmid DNA in sensitive, but not in immune bacteria. None of the colicins E1, E3, E4, E5, E6 or E9 has any influence on bacterial DNA.
Keywords: Chromosomes, Bacterial; Colicins; plazmidy; koliciny; Escherichia coli; Electrophoresis, Agar Gel; DNA, Bacterial; bakteriální chromozomy; elektroforéza v agarovém gelu; Plasmids; DNA bakterií